2014
DOI: 10.1152/ajpregu.00555.2013
|View full text |Cite
|
Sign up to set email alerts
|

D1-like dopamine receptors downregulate Na+-K+-ATPase activity and increase cAMP production in the posterior gills of the blue crabCallinectes sapidus

Abstract: Dopamine-mediated regulation of Na+-K+-ATPase activity in the posterior gills of some crustaceans has been reported to be involved in osmoregulation. The dopamine receptors of invertebrates are classified into three groups based on their structure and pharmacology: D1- and D2-like receptors and a distinct invertebrate receptor subtype (INDR). We tested the hypothesis that a D1-like receptor is expressed in the blue crab Callinectes sapidus and regulates Na+-K+-ATPase activity. RT-PCR, using degenerate primers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It's been shown that the activation of D1Rs inhibit the Na + K + -ATPase through PKA and PKC signaling pathways in striatum [34,35] (Fig. 1), it's also been shown that D1Rs are related with sodium homeostasis in the kidney [7,36], where D1Rs might play an important role in nephropathy that we will briefly discuss later.…”
Section: Aging and Disease • Volume 6 Number 5 October 2015 352mentioning
confidence: 99%
“…It's been shown that the activation of D1Rs inhibit the Na + K + -ATPase through PKA and PKC signaling pathways in striatum [34,35] (Fig. 1), it's also been shown that D1Rs are related with sodium homeostasis in the kidney [7,36], where D1Rs might play an important role in nephropathy that we will briefly discuss later.…”
Section: Aging and Disease • Volume 6 Number 5 October 2015 352mentioning
confidence: 99%
“…Previous studies have shown that cAMP and DAG, as second messengers, affect specific immunity by regulating PKA and PKC activities [21,22]. In the blue crab Callinectes sapidus, D1-like dopamine receptors increased the production of cAMP in the posterior gills [23].…”
Section: Discussionmentioning
confidence: 98%
“…This regulatory mechanism according to Clark, Khan, and Baro (2008) and Therien and Blostein (2000) entails G-proteins that are coupled to D 1 receptors like protein kinase C and the associated pathways that promote the formation of cAMP. The mechanistic details of the role or involvement of protein kinases in the regulation of Na + /K + -ATPase involves the stimulation of adenyl cyclase activity by dopamine D 1 receptors to increase cAMP formation unlike D 2 -like receptors, to promote phosphorylation of Na + /K + -ATPase and consequent internalization or endocytosis and inactivation of the enzyme (Clark et al, 2008;Arnaldo et al, 2014). Endocytosis of the sodium pump as a means of inhibiting Na + /K + -ATPase other than direct phosphorylation has also been reported in Xenopus (Vasilets, Schmalzing, Madefessel, Hamse, & Schmalzing, 1990).…”
Section: Discussionmentioning
confidence: 99%